2009
DOI: 10.1080/09397140.2009.10638330
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to knowledge of the tachinid fly fauna of Fars province, Iran (Diptera: Tachinidae: Dexiinae and Phasiinae)

Abstract: Data are given on the distribution of 18 species of Tachinidae collected from Fars province, 9 of which are new for Iran and all of which are reported for the first time from Fars province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Oriental -China (West); Palaearctic -Europe: East Europe (Czech Republic, Hungary, Poland, Romania, Slovakia, Ukraine), Scandinavia (Denmark, Sweden), South Europe (Bulgaria, Greece, Italy, Turkey), West Europe (Austria, Germany), Middle East (Israel), Mongolia, Russia, Transcaucasia. (O'Hara et al, 2020), Iran (Gheibi et al, 2009).…”
Section: Distributionmentioning
confidence: 99%
“…Oriental -China (West); Palaearctic -Europe: East Europe (Czech Republic, Hungary, Poland, Romania, Slovakia, Ukraine), Scandinavia (Denmark, Sweden), South Europe (Bulgaria, Greece, Italy, Turkey), West Europe (Austria, Germany), Middle East (Israel), Mongolia, Russia, Transcaucasia. (O'Hara et al, 2020), Iran (Gheibi et al, 2009).…”
Section: Distributionmentioning
confidence: 99%
“…The Palaearctic region includes more than 2100 tachinid species and is considered one of the richest geographical regions with about 874, 706, 334 and 198 species belonging to the subfamilies Exoristinae, Tachininae, Dexiinae and Phasiinae respectively (Tschorsnig & Richter, 1998;O'Hara et al, 2020). Over the past two decades the taxonomy of the Iranian tachinids has been increasingly improved and become better known, thanks to the discovery and description of a number of new species from previously poorly studied areas (Tschorsnig, 2000;Richter, 2001;Gheibi et al, 2009Gheibi et al, , 2010Gilasian et al, 2013aGilasian et al, , 2013bGilasian et al, , 2014aGilasian et al, , 2014bGilasian et al, , 2016Gilasian et al, , 2017Gilasian et al, , 2018Gilasian et al, , 2019Gilasian et al, , 2021Seyyedi Sahebari et al, 2014a, 2018a, 2018bZiegler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Later, HERTING (1984) added Estheria pallicornis (LOEW, 1873) and PARCHAMI ARAGHI (1995) reported the species Voria ruralis (FALLÉN, 1810) as a parasitoid of larval Autographa gamma (LINNAEUS, 1758). GHEIBI et al (2008GHEIBI et al ( , 2009 reported four species -Athrycia impressa (VAN DER WULP, 1869), Cyrtophloeba ruricola (MEIGEN, 1824), Periscepsia carbonaria (PANZER, 1798) and Thelaira solivaga (HARRIS, 1780)from Fars province. ZIEGLER et al (2016) described the subspecies of Dinera fuscata occidentalis ZIEGLER, 2013 from Mazandaran and East Azerbaijan provinces.…”
Section: Introductionmentioning
confidence: 99%